2014
DOI: 10.1002/14651858.cd007467.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum antibiotics for known maternal Group B streptococcal colonization

Abstract: Intrapartum antibiotic prophylaxis appeared to reduce EOGBSD, but this result may well be due to bias as we found a high risk of bias for one or more key domains in the study methodology and execution. There is lack of evidence from well designed and conducted trials to recommend IAP to reduce neonatal EOGBSD.Ideally the effectiveness of IAP to reduce neonatal GBS infections should be studied in adequately sized double-blind controlled trials. The opportunity to conduct such trials has likely been lost, as pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
1
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 72 publications
1
42
1
6
Order By: Relevance
“…By reading the abstracts and using our criteria, 41 studies were selected for detailed evaluation; 30 studies were excluded for the reasons noted in Figure 1. Three studies were included through manual searches of the relevant systematic reviews and reference list (Egarter et al, 1996; Benitz et al, 1999; Ohlsson and Shah, 2014). Finally, 14 studies were included in the final analysis (Yow et al, 1979; Easmon et al, 1983; Boyer and Gotoff, 1986; Lim et al, 1986; Tuppurainen and Hallman, 1989; Matorras et al, 1991; Gervasio et al, 2001; EI Helali et al, 2009; Li and Meng, 2010; Shen et al, 2012; Bai, 2014; Ma et al, 2014; Yang, 2015; Zhang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…By reading the abstracts and using our criteria, 41 studies were selected for detailed evaluation; 30 studies were excluded for the reasons noted in Figure 1. Three studies were included through manual searches of the relevant systematic reviews and reference list (Egarter et al, 1996; Benitz et al, 1999; Ohlsson and Shah, 2014). Finally, 14 studies were included in the final analysis (Yow et al, 1979; Easmon et al, 1983; Boyer and Gotoff, 1986; Lim et al, 1986; Tuppurainen and Hallman, 1989; Matorras et al, 1991; Gervasio et al, 2001; EI Helali et al, 2009; Li and Meng, 2010; Shen et al, 2012; Bai, 2014; Ma et al, 2014; Yang, 2015; Zhang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…39 Clinical trials in the 1980s demonstrated that IAP reduced the incidence of early neonatal GBS disease and has formed the basis of IAP strategy 4041 A Cochrane review highlighted a statistically significant reduction in the early-onset neonatal GBS disease following IAP compared with no treatment, where in industrialised countries the number needed to treat to benefit was 25 (95% CI 14 to 100) 42…”
Section: Intravenous Intrapartum Antibiotic Strategy To Prevent Earlymentioning
confidence: 99%
“…1,2 Intrapartum antibiotic prophylaxis for GBS-colonized women has resulted in a significant reduction in early-onset neonatal GBS infection. 3 The obstetric and pediatric GBS guidelines, released in 2010 and 2011, respectively, by the Centers for Disease Control and Prevention (CDC) state that "penicillin remains the agent of choice for intrapartum antibiotic prophylaxis, with ampicillin as an acceptable alternative. Penicillin-allergic women who do not have a history of anaphylaxis, angioedema, respiratory distress or urticaria following administration of a penicillin or cephalosporin should receive cefazolin."…”
mentioning
confidence: 99%